Effect of procainamide on ultrastructure of blood platelet in rabbits - Liu Lian-Pu; Shan Chun-Wen; Liu Xi-Hong; Xiao Huan-Cai; Yang Shu-Qin (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of procainamide (PA) on the ultrastructure of blood platelets. METHODS: Arachidonic acid was added to PA-treated platelet-rich plasma to induce platelet aggregation. The 50-nm sections were examined with a transmission electron microscope. RESULTS: PA 8.5-136 mumol.L-1 markedly inhibited changes of pseudopods, alpha-granules, dense granules, glycogens, open canalicular system, and dense tubular system. CONCLUSION: PA markedly inhibited the changes of ultrastructure of blood platelet and releasing response.